Crypto-politics and counterfeit democracy - Leah Downey; Stefan Eich (Finance and Society, 2023)
What began with an intense bout of crypto fever has since the onset of the pandemic engendered an explosive rise in online retail trading. While the original political promise of financial decentralization has become ever harder to sustain, the idea of democracy as access, including access to highly speculative and gamified investments, continues to capture the financial imagination.
Keywords: 300; crypto; democratization; gamification; Retail finance; Robinhood; speculation